2022
DOI: 10.3389/fmed.2022.852998
|View full text |Cite
|
Sign up to set email alerts
|

Is There Less Alteration of Smell Sensation in Patients With Omicron SARS-CoV-2 Variant Infection?

Abstract: The ongoing pandemic Coronavirus Disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a matter of global concern in terms of public health Within the symptoms secondary to SARS-CoV-2 infection, hyposmia and anosmia have emerged as characteristic symptoms during the onset of the pandemic. Although many researchers have investigated the etiopathogenesis of this phenomenon, the main cause is not clear. The appearance of the new variant of concern Omicron has meant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 61 publications
0
29
0
1
Order By: Relevance
“…However, several studies have shown that in mice and hamsters respiratory disease is less severe after inoculation with Omicron BA.1 variant compared to earlier variants [9][10][11][12], and epidemiological data suggest that hospitalization rates are lower with the Omicron BA.1 variant compared to earlier SARS-CoV-2 variants [13,14]. Indirect evidence suggest that neurological complications in humans might be less common after infection with Omicron BA.1 compared to earlier variants such as D614G or the Delta variant, since both anosmia and Long Covid occur less frequently, although this might be-in part-related to pre-existing immunity [15][16][17][18]. A recent study in transgenic mice-in which ACE-2 expression is higher in the brain compared to the human brain [19,20] -shows frequent neuroinvasion and neurovirulence of D614G and Delta variant but not Omicron BA.1 [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that in mice and hamsters respiratory disease is less severe after inoculation with Omicron BA.1 variant compared to earlier variants [9][10][11][12], and epidemiological data suggest that hospitalization rates are lower with the Omicron BA.1 variant compared to earlier SARS-CoV-2 variants [13,14]. Indirect evidence suggest that neurological complications in humans might be less common after infection with Omicron BA.1 compared to earlier variants such as D614G or the Delta variant, since both anosmia and Long Covid occur less frequently, although this might be-in part-related to pre-existing immunity [15][16][17][18]. A recent study in transgenic mice-in which ACE-2 expression is higher in the brain compared to the human brain [19,20] -shows frequent neuroinvasion and neurovirulence of D614G and Delta variant but not Omicron BA.1 [21].…”
Section: Introductionmentioning
confidence: 99%
“…In general, evidence is accumulating that chemosensory dysfunction occurs less frequently in more recent variants with a prevalence of only 4–33% in Omicron [ 5 , 6 , 54 , 60 ]. This may be due to modifications in the spike protein and herewith reduced interaction with proteins of the olfactory epithelium responsible for virus uptake, such as angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2) [ 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism by Rodriguez-Sevilla et al alludes to the significance of previous immunity among those infected by Omicron, postulating that re-infection in previously exposed populations would lead to a diminished systemic and local inflammatory response, causing less cellular damage in the olfactory epithelium. [ 33 ]…”
Section: Methodsmentioning
confidence: 99%